2016
DOI: 10.5455/medarh.2016.70.208-212
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Prevalence and Risk Factors of Non-communicable Diseases in the Albanian Adult Population

Abstract: Aim:There is growing evidence that non-communicable diseases (NCDs) are a major health problem in developing and transitional countries. The prevalence of NCDs and associated factors are under-researched in Albania. We aimed to assess the prevalence and socio-demographic and lifestyle correlates of NCDs in the Albanian adult population.Methods:The study was carried out in the framework of Albania Living Standard Measurement Survey (LSMS), a national population-based cross-sectional study conducted in 2012 incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
3
7
0
1
Order By: Relevance
“…The current study also found that the prevalence of all four chronic diseases increased with age, likewise found in other studies [ 30 , 31 ]. As such young adults and middle age should be made known of the alarming trend and statistic in order for them to consider healthier lifestyles to achieve healthy aging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study also found that the prevalence of all four chronic diseases increased with age, likewise found in other studies [ 30 , 31 ]. As such young adults and middle age should be made known of the alarming trend and statistic in order for them to consider healthier lifestyles to achieve healthy aging.…”
Section: Discussionsupporting
confidence: 92%
“…Body mass index (BMI) has routinely been considered a risk factor for chronic conditions [ 31 , 33 , 34 ]. Although the prevalence of being overweight or obese individuals in Haikou was lower than the average in China [ 36 ], overweight and obesity have increasing become a major public health problem nationwide in China.…”
Section: Discussionmentioning
confidence: 99%
“…16 Fertilizer and other agrochemicals, atmospheric deposition, and irrigation with contaminated water have also been implicated in Pb contamination of crops. 44 Similarly high Cd concentrations were found in leafy vegetables sampled at Dabaoshan mine 45 and at Bac Kan. 16 Other studies have found lower 6,46 and higher 47,48 Cd concentrations in vegetables compared to those found in our study.…”
Section: Heavy Metal In Vegetables In Sampling Sitessupporting
confidence: 74%
“…Em relação à escolaridade, encontrou-se maior prevalência de DCNT entre aqueles com menos de oito anos de estudo. Achados semelhantes foram identificados em pesquisas nacionais e internacionais [25][26][27][28] . De acordo com Braveman et al 29 , as pessoas com menos escolaridade e que vivem em localizações geográficas menos favorecidas, são desproporcionalmente afetadas por doenças crônicas, muitas vezes como resultado de desvantagens sociais e maior vulnerabilidade.…”
Section: Discussionunclassified